Tren dan Pola Penentu Pemilihan Destinasi Wisatawan Domestik Generasi Z di Negara Berkembang: Pendekatan Systematic Literature Review (SLR) - Sari Bulan; Ismanto Ismanto; Hanif Kurniadi (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Understanding the factors influencing Generation Z's domestic tourist destination choices in developing countries remains fragmented and scattered across various research contexts, thus lacking a comprehensive and integrated picture. This study aims to identify trends and patterns in the determinants of Generation Z domestic tourist destination choices in developing countries through a Systematic Literature Review (SLR) approach. The literature search was conducted systematically in ScienceDirect, Google Scholar, SpringerLink, and the Directory of Open Access Journals (DOAJ) databases for publications from 2018–2025, following the PRISMA guidelines. Of the 1,031 identified articles, ten met the inclusion criteria and were analyzed in depth through screening, eligibility evaluation, and synthesis of findings. The analysis revealed that psychodigital factors were the most dominant determinants in shaping Generation Z's travel intentions and decisions, including the quality of digital information, telepresence, social media marketing, TikTok content, and the use of digital tourism. Theoretical frameworks such as Stimulus–Organism–Response (SOR), Theory of Planned Behavior (TPB), and the concept of risk perception explain how digital stimuli influence young tourists' cognitive and affective processes in evaluating and selecting tourist destinations. Furthermore, socio-demographic characteristics and post-pandemic dynamics also strengthen the variations in destination selection behavior among Generation Z. The findings of this study emphasize that the integration of psychodigital elements needs to be the main basis in formulating marketing strategies and domestic tourism development policies in developing countries to be more adaptive to the characteristics and preferences of Generation Z.